Necrotizing Fasciitis in Forearm : Case Report and Literature Review - BOZKURT, Mehmet; ZOR, Fatih; KÜLAHÇI, Yalçın; BENLİER, Erol (Cerrahpaşa Medical Journal, 2014)
Necrotising fasciitis is a rapid, aggressive and life-threatening infection of the soft tissues characterized by the spread of infection and necrosis through the fascia and subcutaneous fat. It may be either a pure group A streptococcal infection or a polymicrobial infection. Necrotising fasciitis is relatively uncommon in children. It usually affects previously healthy children with no underlying predisposition to infection. By contrast, in adults necrotising fasciitis usually affects those with a pre-existing medical condition and often follows an inciting event such a severe soft-tissue trauma. Necrotising fasciitis has a very high mortality rate, with the highest incidence of deaths reported in the elderly, debilitated, diabetic patients, and neonates with necrotising fasciitis involving the abdominal wall. We present a rare case of necrotising fasciitis in an adult who had not predisposing factor for necrotizing fasciitis except chronic self-mutilation in his forearm. The etiology, diagnosis and management of necrotising fasciitis in forearm is being discussed in adults. Early diagnosis, intravenous antibiotics and aggressive surgical debridement are mandatory for an optimal outcome.